The Renaissance of Unicompartmental Knee Arthroplasty appears rational - A radiograph-based comparative Study on adverse Events and patient-reported Outcomes in 353 TKAs and 98 UKAs. - Magnus Tveit (Public Library of Science (PLoS), 2021)
Purpose Total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA) are both considered suitable for antero-medial osteoarthritis and spontaneous osteonecrosis of the knee. National registry data are consistent in showing higher revision rates for UKA. Adequately adjusted, these findings may be challenged by differences in adverse events and patient-reported outcomes, as both can have serious long-term implications. Based on preoperative radiographs, the aim was to retrospectively compare the two principle surgeries in these respects. Methods All TKA procedures in 2016 in one Swedish county council were, according to certain radiograph-based consensus criteria, visually evaluated for medial UKA suitability. Then, using different regression models, they were compared with the corresponding medial UKAs performed in 2015-2017 regarding complications and patient-reported outcomes one year after surgery. Results The UKA group showed an 82% reduced risk (OR 0.2; 95% CI 0.0-0.6) of any complications, whereas the 55% reduced risk of severe complication did not reach statistical significance (OR 0.5; 95% CI 0.1-2.1). These findings corresponded in high-volume surgeries to an absolute complication rate of 0% in the UKA group and 10% in the TKA group (p = 0.005) and to a severe complication rate of 0% and 5% respectively (p = 0.05). Though no differences were seen in any general patient-reported outcomes, the pain and function based OMERACT-OARSI responder criteria indicated in both around a 60% better chance of any response (OR 1.6 CI % 0.6-4.5) and a high response (OR 1.6; 95% CI 0.7-3.4) in the UKA group. Conclusion No differences were shown in patient-reported outcomes but a clear difference in risk of complications, favoring the UKA procedure.